Efektifitas Perencanaan Pembelajaran PAI dengan Pendekatan STEAM Education dalam Membentuk Kolaborasi dan Kreatifitas Siswa di SMP Al-Ashar Tangerang - Muhammad Ilhamsyah Akbar; Nafis Syafudin; Siti Uusnawati; Najmi Aulia; Wihda Alny Mawaddah (Penerbit Minhaj Pustaka, 2026)
This study highlights the STEAM approach as a meaningful innovation in Islamic Education learning at Al-Ashar Junior High School, aiming to integrate science, technology, engineering, art, and mathematics to enhance students' learning experiences. The research methods included field observations and qualitative descriptive analysis, focusing on the implementation of STEAM in Islamic Education learning. The results show that the STEAM approach, through projects such as the Islamic Art Exhibition and the use of Canva, is relevant in developing students' creativity, collaboration, and motivation to learn. The evaluation reveals an increase in critical thinking and problem-solving skills, although challenges such as limited technological skills and adaptation to the new curriculum still exist. In conclusion, with teacher support and the appropriate use of technology, STEAM has proven effective in making PAI learning more engaging, relevant, and aligned with the characteristics of Generation Z and Alpha, placing students at the centre of learning and encouraging active participation in the learning process. Abstrak Penelitian ini menyoroti pendekatan STEAM sebagai inovasi bermakna dalam pembelajaran PAI di SMP Al-Ashar, bertujuan mengintegrasikan sains, teknologi, teknik, seni, dan matematika untuk meningkatkan pengalaman belajar siswa. Metode penelitian meliputi observasi lapangan dan analisis deskriptif kualitatif, dengan fokus pada implementasi STEAM dalam pembelajaran PAI. Hasil penelitian menunjukkan bahwa pendekatan STEAM, melalui proyek seperti Islamic Art Exhibition dan pemanfaatan Canva, relevan dalam mengembangkan kreativitas, kolaborasi, dan motivasi belajar siswa. Evaluasi mengungkapkan peningkatan kemampuan berpikir kritis dan pemecahan masalah, meskipun tantangan seperti keterbatasan keterampilan teknologi dan adaptasi kurikulum baru masih ada. Kesimpulannya, dengan dukungan guru dan penggunaan teknologi yang tepat, STEAM terbukti efektif dalam membuat pembelajaran PAI lebih menarik, relevan, dan sesuai dengan karakteristik generasi Z dan Alpha, menjadikan siswa sebagai pusat pembelajaran dan mendorong partisipasi aktif dalam proses belajar.